PENERAPAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATEMATIKA MELALUI TEACHING AT THE RIGHT LEVEL - Nurmala, Inur; Rahaju, Endah Budi; Wahyuni, Indah Saptaning (Universitas Insan Budi Utomo, 2025)
Mathematics is a very important subject to learn, but the reality is that currently students consider mathematics to be a difficult subject to understand. So, the aim ’s of this research is to determine the increase in students’ cognitive learning outcomes in mathematics learning using the Problem Based Learning model through the Teaching at The Right Level approach in class X Office Management 1 students of SMKN 1 Surabaya in the odd semester of the 2024/2025 academic year. The data collection method uses observation and learning outcome tests. The learning outcomes of 36 students showed an average score of 55.88 in the pre-cycle, with 33.33% of students achieving a passing grade. The average score in Cycle I was 70.84, with 55.56% of students achieving a passing grade, and the average score in Cycle II was 81.59, with 83.33% of students achieving a passing grade. This study can be concluded that the application of the Problem Based Learning model through the Teaching at The Right Level approach can improve students' cognitive mathematics learning outcomes.